Strategy as an intertextual narrative: a tale of fear and hope in the setting of higher education in the UK - Holstein, Jeannie C. A. (2015)
This is a study about strategy. It uses the relatively underdeveloped but promising concept of narrative infrastructure to address a gap in understanding (Fenton and Langley, 2011) in how strategy as an intertextual narrative acquires stability and routine. Studies that have considered strategy as an intertextual narrative have largely been in settings in which strategy is made toward an unequivocal direction, within a relatively short time horizon (Llewellyn, 2001; Vaara et al., 2006; Riad et al., 2012). Framing to support availability and resonance of narrative building blocks, as part of the centralisation of meaning in strategy as an intertextual narrative, whilst evident (Vaara et al., 2004; Vaara et al., 2006; Riad, et al., 2012) is nonetheless underexplored. In response, this study considers strategy in the setting of higher education (HE) in the UK, where there is a greater plurivocality, in terms of multiple voices, at different levels, and a wider temporality. In a narrative enquiry in two research-intensive universities in the UK, including a review of policy documents (1992-2012), the study demonstrates how strategy achieves cohesion through powerful narrative framing, so that direction and thrust is maintained. It also provides one explanation of how strategy may unwind over time. Insight is gained because the three different facets– constitutive, manifest and ideological – of intertextuality have been considered (Riad et al., 2012). Notably, by examining manifest intertextuality, it shows that strategy is framed in a context of agitation and in an emotional register of fear and hope, extending the work of Riad et al., 2012. It also shows how in ideological intertextuality powerful framing, in which both wider plurivocality and greater temporality is apparently maintained, strategy endures.